Consideration of nutrients of public health concern highlighted in the Dietary Guidelines for Americans 2020–2025 among a large sample of US primary shoppers. (1st February 2023) - Gustafson, Christopher R.; Rose, Devin J.
Abstract: The objective of this research is to estimate the proportion of consumers who consider nutrients identified in the Dietary Guidelines for Americans 2020-2025 ( DGA ) as being of public health concern during food choice using a large, population-weighted sample of U.S. residents. A question was included in a bi-monthly survey of consumer scanner panel members, asking whether respondents considered each of eight nutrients in a check-all-that-apply format. Four of these nutrients are under-consumed nutrients, while three are nutrients to avoid. Calories was additionally included, as over-consumption of calories causes weight gain. Weighted mean proportions and 95% confidence intervals were estimated. The survey was administered to a population-weighted sample of 42, 018 US consumers participating in a consumer scanner panel in May–June 2021 by an online survey firm that maintains the consumer panel. Over one-quarter of respondents considered none of the nutrients. Each under-consumed nutrient of public health concern was considered by less than 30% of respondents, ranging from a low of 14.5% for potassium (95%CI = 14.3–14.7%) to a high of 28.9% for dietary fiber (95%CI = 28.7–29.1%). Nutrients to be avoided were considered by higher percentages of the sample, ranging from 31.8% for saturated fats (95%CI = 31.6–32.0%) to 46.1% for added sugars (95%CI = 45.8–46.3%). Respondents considered an average of just over 2.4 total nutrients, with a greater focus on nutrients to avoid, including calories (weighted mean = 1.55), than under-consumed nutrients (weighted mean = 0.89). Over one-quarter of consumers considered no nutrients of public health concern. Consumers focused more on nutrients to avoid rather than under-consumed nutrients. Promoting increased awareness of important under-consumed nutrients may improve public health.